A simple method for analysis of Saccharomyces cerevisiae morphology by applying a high vacuum mode of the scanning electron microscopy and without chemical fixatives. Issue 1 (March 2020) - Karimy, M F; Damayanti, E; Suryani, A E; Prasetyo, E; Nurhayati, R; Anwar, M; Anggraeni, A S
Abstract: A simple method for the preparation of a specimen for observing Saccharomyces cerevisiae B-18 by using a high vacuum mode setting of scanning electron microscopy (SEM). The method without chemical fixatives (F0) was very simple, the culture was directly taken from Chloramphenicol Yeast Glucose Agar (CYGA) by using a loop needle and coated with a film of gold (Au) without using any chemical fixative and only air dehydrating procedures. The method with chemical fixatives (F1) like osmium tetroxide (OsO4), is highly toxic and corrosive. The methods also take much time for the preparation of samples before observation. The morphology of S. cerevisiae B-18 was observed of two magnifications, 5K and 10 K and over a range of time setting of ion sputter and one current that is ten mA. The treatments of ion sputter current exposure in this study were ten mA for 10 (T10), 20 (T20), 30 (T30), 40 (T40), 50 (T50), and 60 (T60) seconds. This preparation procedure could be most useful for S. cerevisiae morphological screening of rapidly and safely than using chemical fixatives before using adequate preparation procedure with chemical fixatives and could substitute light microscopy method with better magnification. The best result is the ion sputter setting ten mA for 60 seconds (T60) without any charging phenomenon disturbances. We have suggestions for F0; the first is the maximum duration of the sample that had air-dried is about three hours because more than its period, the resolution would be not proper. The optimum period for observation in the chamber in the high vacuum condition is about two hours and the second to developing methods so that representation for cell diameter measurements can be even better than this study.